Saccular Cyst of the Larynx - A Clinical Case - Fedir Yurochko; Dzvenyslava Kopanska; Taras Tsolko; Wojciech Domka (International Journal of Medical Science and Clinical Research Studies, 2023)
Saccular cyst of the larynx is a benign supraglottic lesion, filled with mucus. It forms from the laryngeal sac, which is a soft tissue mass that is an extension of the laryngeal ventricle. Due to the extreme rarity, the true prevalence of the disease is unknown, although congenital laryngeal cysts have been reported to affect 1 in 300,000 newborns. The gold standard for diagnosing of saccular laryngeal cysts is laryngoscopy. Treatment of saccular cysts can only be done surgically, using endoscopic or external access. It is believed that endoscopic CO2 laser excision is the treatment of choice.